Transcription Defines the Embryonic Domains of Cis-Regulatory Activity at the Drosophila Bithorax Complex - Drewell, Robert A.; Bae, Esther; Burr, John; Lewis, Edward B. (Proceedings of the National Academy of Sciences - PNAS, 2002)
The extensive infraabdominal (iab) region contains a number of cis-regulatory elements, including enhancers, silencers, and insulators responsible for directing the developmental expression of the abdominal-A and Abdominal-B homeotic genes at the Drosophila bithorax complex. It is unclear how these regulatory elements are primed for activity early in embryogenesis, but the 100-kb intergenic region is subject to a complex transcriptional program. Here, we use molecular and genetic methods to examine the functional activity of the RNAs produced from this region and their role in cis regulation. We show that a subset of these transcripts demonstrates a distinct pattern of cellular localization. Furthermore, the transcripts from each iab region are discrete and the transcripts do not spread across the insulator elements that delineate the iab regions. In embryos carrying a Mcp deletion, the intergenic transcription pattern is disrupted in the iab4 region and the fourth abdominal segment is transformed into the fifth. We propose that intergenic transcription is required early in embryogenesis to initiate the activation of the Drosophila bithorax complex and define the domains of activity for the iab cis-regulatory elements. We also discuss a possible mechanism by which this may occur.